Academic activity, technology and social network: the behavior of generation Z (Research, Society and Development, 2020)
This paper aims to analyze the habits and attitudes of academics in relation to the social networks and how they are used, as well as how much they feel harmed by the excessive use of technology. Thus, bibliographic sources such as books and scientific articles were used. As for the nature of the variables, this is a quantitative and exploratory research. The research was carried out with 100 academics through a personal interview. The main findings of the research found that academics use Whatsapp more (96%), mainly with personal relationships purposes, with 94% (always and sometimes), and study comes next, with 85%. Still as a finding, 71% have more than 100 contacts, and 64% have up to 10 groups on Whatsapp. Finally, it was possible to identify that 63% of the interviewees already felt harmed by the excessive use of technology.